PENERAPAN FAULT TREE ANALYSIS (FTA) TERHADAP FAKTOR KETERLAMBATAN PENYELESAIAN PROYEK RENOVASI INTERIOR - Denata, Fian Azis; Puspaningrum, Astrid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
PT Prima Daya Nugraha is a contractor specialized in mechanical, Electrical & HVAC, established in 2013. The satisfaction of partners and customers is its business strategy for growth and development. As the company progresses, it opened a new business area in 2022, i.e., interior project. The company has taken an interior job and renovation project for Matahari Department Store Festival Citylink in Bandung and Matahari Department Store Uptown in Semarang. The object of this qualitative descriptive research is the interior renovation project of Matahari Department Store Festival Citylink in Bandung. The completion of this project was delayed, but the contractor company faced difficulties in analyzing factors that had caused the delay. Therefore, fault Tree Analysis (FTA), a qualitative analytical tool, is needed. The analysis was conducted in stages of identifying problems that had caused the delay, making the fault tree construct diagrams along with the logic gate from the basic event to the top event. The stages have enabled the analysis on factors causing the delay, the identification of fault event combination, i.e., the minimal cut set, that had led to the occurrence of the top event, the qualitative fault tree analysis using the Boolean algebra to acquire the minimal cut set, and the identification of events causing the top event.